MEMBANGUN STRATEGI MANAGEMENT UMKM GUNA MENINGKATKAN PERTUMBUHAN EKONOMI DIKELURAHAN CISARUA - Enjang, Enjang; Asarudin, Ahmad; Luki, M; Albarjanji, Rizki (ABISATYA DINAMIKA ISWARA PUBLISHING, 2023)
Student Work Class (KKM) is a form of community service carried out by students in an interdisciplinary, institutional, and partnership manner as one of the manifestations of STIE PASIM SUKABUMI. The community service program is seen as a program that must be implemented, both by lecturers and by students, based on the principles of academic, entrepreneurial, and professional competence, so as to produce quality, relevant, and synergistic community service programs in increase community empowerment. This study aims to analyze the role of priority community service abd the influence of the spirit of motivation and the spirit of community awareness on UMKM through seminars in the Cisarua sub-district, Sukabumi city.